2013
DOI: 10.1371/journal.pone.0083164
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Severe Wasp Sting Patients with Dominantly Toxic Reaction: Analysis of 1091 Cases

Abstract: BackgroundMassive wasp stings have been greatly underestimated and have not been systematically studied. The aim of this study was to identify the clinical features and treatment strategies of severe wasp stings.Methods and FindingsA multicenter retrospective study was undertaken in 35 hospitals and medical centers including 12 tertiary care hospitals and 23 secondary care hospitals in the Hubei Province, China. The detailed clinical data of 1091 hospitalized wasp sting patients were investigated. Over three-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(126 citation statements)
references
References 19 publications
(16 reference statements)
10
116
0
Order By: Relevance
“…However, only a few studies have reported the use of blood purification for venom-induced MODS treatment. In the medical literature, the largest case series reporting the treatment with blood purification on venom-induced MODS included 119 patients [2] . Notably, there was no data regarding the effect of blood purification on mortality or disease progression of venom-induced MODS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a few studies have reported the use of blood purification for venom-induced MODS treatment. In the medical literature, the largest case series reporting the treatment with blood purification on venom-induced MODS included 119 patients [2] . Notably, there was no data regarding the effect of blood purification on mortality or disease progression of venom-induced MODS.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, almost all patients who have suffered from a single or a few stings have had IgE-mediated allergic reactions of different degrees [1] . Thus, it is rare for them to develop renal failure and MODS [2] . In such cases, treatment is centered on controlling the allergic reaction and desensitization [3,4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bee and wasp stings are common insults for CA-AKI in Asia, especially in regions of Southern China, India, Nepal, and Vietnam [43,44,45,46]. One or two stings cause just a local allergic reaction, but massive attacks with hundreds to thousands of stings cause severe systemic symptoms, affecting different organs with a high mortality.…”
Section: Causes and Patterns Of Aki In Asiamentioning
confidence: 99%
“…Wasp stings can cause a variety of symptoms such as local reactions including swelling, redness, heat and pain, and severe wasp venom absorption, can cause fever, dizziness, coma, failure of the heart, liver, kidneys, and even death [1,2]. We performed a retrospective study of 158 patients with wasp stings treated at our hospital from April to November 2014.…”
Section: Introductionmentioning
confidence: 99%